Cold ancestors, bigger predators: maternal and transgenerational temperature effects on Orius laevigatus body size - Ana Belén Abelaira; María del Carmen Reche; Amador Rodríguez-Gómez; Virginia Balanza; Pablo Bielza (Journal of Pest Science, 2026)
Developmental temperature strongly affects insect body size, a key trait for the performance of predators used in augmentative biological control. The anthocorid Orius laevigatus is widely released against thrips in greenhouse crops, and larger individuals show higher fecundity and predation capacity. Here, we analyze how thermal history across generations shapes adult size in this predator, combining genetic improvement and phenotypic plasticity. We compared two cold-tolerant lines of O. laevigatus , previously selected for enhanced performance at low temperature, with a commercial strain. Lineages were reared for four successive generations under combinations of 15 and 26 °C, and pronotum width of adults from the last generation was measured as a proxy of body size. Cold-selected lines were consistently larger than the commercial strain across all treatments, confirming a strong genetic component to size. Developmental temperature in the last generation had the largest effect, with individuals reared at 15 °C being larger than those reared at 26 °C. In addition, exposure of parents, grandparents, and great-grandparents to 15 °C increased the size of descendants, revealing a clear but gradually declining transgenerational effect. However, multiple consecutive cold generations did not further increase size and could even reduce it. These results show that combining cold-selected lines with strategically timed cold rearing can generate larger predators without permanently slowing mass rearing, although prolonged exposure to low temperature may be counterproductive.